Answer:
1/3
Step-by-step explanation:
Answer:
1/5
Step-by-step explanation:
I think thats right idI dont knowk ahaha sorry if its not
He packed 576 apples into the boxes.
31 + 41 = 72 and 72 * 8 = 576
Answer:
18
Step-by-step explanation:
wait check b4 you answer
F(-1)= -3 is (-1,-3) and f(2) = 6 is (2,6) where f(x) = y
y=mx + b is the slope-intercept form whereas m equals the slope (rate of change) and b equals the y-intercept (initial amount/what y is when x is 0.)
First, we need to find the slope between the two points (-1,-3) and (2,6). To find the slope we could use one of it's formulas
![\frac{y^2 - y^1}{x^2 - x^1}](https://tex.z-dn.net/?f=%20%5Cfrac%7By%5E2%20-%20y%5E1%7D%7Bx%5E2%20-%20x%5E1%7D%20)
.
1. (-1,-3)
2. (2,6)
![\frac{6 - -3}{2 - -1}](https://tex.z-dn.net/?f=%20%5Cfrac%7B6%20-%20-3%7D%7B2%20-%20-1%7D%20)
→
![\frac{9}{3}](https://tex.z-dn.net/?f=%20%5Cfrac%7B9%7D%7B3%7D%20)
→
![\frac{3}{1}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B1%7D%20)
The slope is 3 (
![\frac{3}{1}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B1%7D%20)
). Thusly, y = 3x + b
To find out the y-intercept, we can reverse the slope. [Note: This
![\frac{3}{1}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B1%7D%20)
is in
![\frac{rise}{run}](https://tex.z-dn.net/?f=%20%5Cfrac%7Brise%7D%7Brun%7D%20)
where rise is 'y' and run is 'x'. Reversed would be
![\frac{-3}{-1}](https://tex.z-dn.net/?f=%20%5Cfrac%7B-3%7D%7B-1%7D%20)
]. Take the second ordered pair and use our reversed slope on it until we get 0 for x.
(2, 6) ⇒ (2 - 1, 6 -3) ⇒ (1, 3) ⇒ (0,0)
Y-intercept is 0. Therefore,
y= 3x + 0 [NOTE: y = f(x), so if you want it in function notation form it's just f(x) = 3x + 0.]